Sub-pixel analysis to enhance the accuracy of evapotranspiration determined using MODIS images - Abd.N., Matori (2017)
A study was carried out to estimate the actual evapotranspiration (ET) over a 1074 km2 of the humid area of Perak State (Malaysia), where water and evaporation cycle deeply influences the climate, natural resources and human living aspects.